Entrepreneurial intention of international business students in Viet Nam: A survey of the country joining the Trans-Pacific Partnership - Cuong Nguyen (Journal of Innovation and Entrepreneurship, 2017)
This study aims to investigate entrepreneurial intention among international business students in Viet Nam as it is on the way to approve The Trans-Pacific Partnership (TPP). The theory of planned behavior (TPB) (Ajzen, 1991) is used to assess the determinants of entrepreneurial intention of Vietnamese students who major in international business study. An exploratory factor analysis and multiple regressions are used to examine the responses from 372 final year students. The results confirm that attitude toward entrepreneurship and perceived behavior control are positively related to entrepreneurial intention. Subjective norm fails to generate a significant impact on entrepreneurial intention. Entrepreneurial intention is significantly influenced by two components of TPB model (R²0.167em=0.167em0.307) which are attitude toward entrepreneurship (β0.167em=0.167em0.292) and perceived behavior control (β0.167em=0.167em0.408).
Keywords: 650; Entrepreneurial intention; Ajzen's planned behavior theory (TPB); International business students; Trans-Pacific Partnership (TPP)